Xanthine Oxidase: Isolation, Assays of Activity, and Inhibition - Danijela A. Kostić; Danica S. Dimitrijević; Gordana S. Stojanović; Ivan R. Palić; Aleksandra S. Đorđević; Jovana D. Ickovski (Journal of Chemistry)
Xanthine oxidase (XO) is an important enzyme catalyzing the hydroxylation of hypoxanthine to xanthine and xanthine to uric acid which is excreted by kidneys. Excessive production and/or inadequate excretion of uric acid results in hyperuricemia. This paper presents a detailed review of methods of isolation, determination of xanthine oxidase activity, and the effect of plant extracts and their constituents on it. Determining the content and activities of XO can be used for diagnostic purposes. Testing inhibition of XO is important for detection of potentially effective compounds or extracts that can be used to treat diseases that are caused by increased activity of XO. In vitro bioassays are used to examine test material for XO inhibition, as inhibitors of XO may be potentially useful for the treatment of gout or other XO induced diseases. Several authors reported on the XO inhibitory potential of traditionally used medicinal plants.